Letter from the United States Commercial Representative to the Speaker of the United States House of Representatives - B. Zoellick, Robert (2016)
In accordance with section 2104 (a) (1) of the Trade Act 2002 (the Trade Act), and in accordance with the authority delegated to me by the President, I am pleased to notify Congress that the President intends to Start negotiations of a Free Trade Agreement (FTA) with Colombia, Peru, Ecuador, and Bolivia, the four beneficiaries of the Andean Trade Preference Law (ATPA).